KEJADIAN DIARE PADA MASYARAKAT PETERNAK SAPI PERAH - Redhita Fatrisia; Endang Sri Redjeki; Rara Warih Gayatri (Preventia : The Indonesian Journal of Public Health, 2017)
ABSTRACT : Diarrhea is still a global public health problem especially in developing countries like Indonesia. Diarrhea is closely related to environmental health. The purpose of this study was to determine the relationship between diarrhea occurrence with the density of flies and the management of livestock waste in dairy farmers community in Krajan Hamlet, Kemiri Village, Jabung District, Malang Regency. The type of this research is descriptive analytic with cross sectional study design. The data were collected using questionnaires, observation sheets, and measurement using fly grill and hand counter. The sample in this research is 177 dairy farmer families with sampling method using cluster random sampling. Data were analyzed by univariate and bivariate analysis using chi square test. The results showed a significant correlation between diarrhea occurrence with flies density (p = 0.00) and there was significant correlation between diarrhea occurrence and livestock waste management (p = 0.00). It is suggested to the dairy farmers community to apply clean and healthy behavior, and to conduct the management and utilization of livestock waste.Keyword : the incidence of diarrhea, fly density, the management of livestock wasteABSTRAK : Diare masih menjadi masalah kesehatan masyarakat dunia, terlebih di negara berkembang seperti Indonesia. Diare erat kaitannya dengan kesehatan lingkungan. Penelitian ini bertujuan untuk mengetahui hubungan antara kejadian diare dengan kepadatan lalat dan pengelolaan limbah ternak pada masyarakat peternak sapi perah di Dusun Krajan, Desa Kemiri, Kecamatan Jabung, Kabupaten Malang. Jenis penelitian adalah deskriptif analitik dengan desain studi cross sectional. Pengumpulan data menggunakan instrumen berupa kuesioner, lembar observasi, dan pengukuran menggunakan fly grill dan hand counter. Sampel pada penelitian ini adalah 177 keluarga peternak dengan metode pengambilan sampel menggunakan cluster random sampling. Data dianalisis dengan analisis univariat dan bivariat menggunakan uji chi square. Hasil penelitian menunjukkan adanya hubungan yang signifikan antara kejadian diare dengan kepadatan lalat (p= 0,00) dan terdapat hubungan yang signifikan antara kejadian diare dengan pengelolaan limbah ternak (p= 0,00). Disarankan kepada masyarakat peternak sapi perah untuk menerapkan Perilaku Hidup Bersih dan Sehat (PHBS), dan melakukan usaha pengelolaan dan pemanfaatan limbah ternak.Kata Kunci : kejadian diare, kepadatan lalat, pengelolaan limbah ternak